Determination of fibromyalgia syndrome in patients with non-cardiac chest pain in accordance with 1990 and 2010 diagnostic criteria - Gülkesen, Arif (My University, 2019)
To determine the frequency of Fibromyalgia syndrome (FMS) in accordance with the American College of Rheumatology (ACR) 1990 and ACR 2010 FMS classification criteria, also to assess the pain intensity, functional and emotional status of patients whoare admitted to the cardiology clinic with a complaint of chest pain without a cardiologic pathology. 107 female patients with chest pain, who admitted to cardiology polyclinic after discarding cardiac chest pain, directed to Physical Medicine and Rehabilitation polyclinic, were included to the study. All patients were assessed in terms of age, height, weight, body mass index (BMI), chronic pain duration, Visual Analog Scale (VAS), Fibromyalgia Impact Questionnaire (FIQ), Widespread Pain Index (WPI), Symptom Severity Scale (SS) and Back Anxiety Depression Scale (BADS). The ACR was assessed according to the 1990 and 2010 FMS classification criteria. It was found that 3(2.8%) of these patients met only the 1990 criteria, 3(2.8%) only met the 2010 criteria and 16(15%) met both the 1990 and 2010 criteria, but 85(79.4) did not meet any of the criteria. The number of tender points, WPI, SS and FIQ values of the clinical and functional evaluation parameters of FMS were higher in the FMS group and this result was statistically significant (p<0.001). The frequency of FMS in patients with non-cardiac chest pain (NCCP) is similar to the frequency of FMS in general population. In patients with NCCP, FMS is a diagnosis that should be taken into account.
Keywords: Genel ve Dahili Tıp; Patoloji; Romatoloji; Kalp ve Kalp Damar Sistemi